2006
DOI: 10.1016/j.crvi.2005.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Elevated total and isoenzyme forms of acid phosphatase in falciparum malaria

Abstract: The activities of total serum acid phosphatase (E.C. 3.1.3.2) and of two of its isoenzymes, tartrate-resistant acid phosphatase and erythrocyte-specific acid phosphatase were measured in 109 adult male and female patients presenting acute falciparum malaria infection, and a normal, healthy control group comprised of 82 subjects. All the three forms of acid phosphatase were found to be significantly (p < 0.05) higher during infection as compared to their activity in the control group. This result suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
(18 reference statements)
3
4
1
Order By: Relevance
“…Increase in ROS and decrease in antioxidants has been reported in malaria patients [14][15][16]. The alterations in the major antioxidants of the erythrocytes and the peroxide lysis of the erythrocytes may result in release of enzyme like ACP [17]. Our results indicate that ACP levels are very highly increased in malaria patients where as Hb levels are decreased.…”
Section: Discussionsupporting
confidence: 64%
“…Increase in ROS and decrease in antioxidants has been reported in malaria patients [14][15][16]. The alterations in the major antioxidants of the erythrocytes and the peroxide lysis of the erythrocytes may result in release of enzyme like ACP [17]. Our results indicate that ACP levels are very highly increased in malaria patients where as Hb levels are decreased.…”
Section: Discussionsupporting
confidence: 64%
“…Similar findings were noted by D'Souza B et al, Garba IH et al, Daniel E et al, Pratinidhi SA et al [4][5][6][7] It has been reported that the red blood cells contain an excess quantity of ACP. The cell membrane plays a central role in the growth and propagation of the malarial parasite in the blood.…”
Section: Discussionsupporting
confidence: 77%
“…[9][10][11] The alterations in the major antioxidants of the erythrocytes and the peroxide mediated lysis of the erythrocytes may result in release of enzymes like ACP. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Our study also shows statistically significant decrease in heamoglobin (Hb) levels between the malarial and non-malarial fever patients. Similar findings were also noted by D'Souza B et al, Kanwar G et al, Garba IH et al, Pratinidhi SA et al [6,7,14,15] .…”
Section: R -Opo 3 +Acceptor --------R -Oh + Acceptor-posupporting
confidence: 78%